Dictators and democracy in African development : the political economy of good governance in Nigeria - LeVan, A. Carl. (New York : Cambridge University Press, 2014)
This book argues that the structure of the policy-making process in Nigeria explains variations in government performance better than other commonly cited factors.
The Aguiyi-Ironsi Regime: A Dictator's Ambitions Checked by a Regional Veto (1966) -- Yakubu Gowon Contends with a Military Council Veto (1966-1975) -- Mohammed/Obasanjo: Three Veto Players and an Unexpected Succession (1975-1979) -- Partisan and Presidential Veto Players during the Second Republic (1979-1981) -- Three Institutional Veto Players and the Second Republic's Swift Decline (1982-1983) -- A Veto from Buhari, a Veto from Idiagbon (1984-1985) -- A Triumvirate of Veto Players during Babangida's Early Years (1985-1990)
Print version record.
Includes bibliographical references (pages 243-274) and index.
eBooks on EBSCOhost
Keywords: Nigeria -- Politics and government; Dictatorship -- Nigeria; Democracy -- Nigeria; Economic development -- Political aspects -- Nigeria; Nigeria -- Economic conditions; Nigeria -- Politique et gouvernement; Dictature -- Nigeria; Développement économique -- Aspect politique -- Nigeria; Nigeria -- Conditions économiques.; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Democracy; Dictatorship; Economic development -- Political aspects; Economic history; Politics and government; Nigeria; Agency-Theorie; Demokratie; Diktatur; Machtmissbrauch; Nigeria